Effects of nicotine on Schizophrenia and antipsychotic medications: a systematic review - Hamdan, Hamira Farahana; Zaini, Syahrir (Malaysian Psychiatric Association, 2018)
Majority people with schizophrenia who smoke cigarettes, tend to be heavy smokers than other psychiatric patients and general population. Nicotine is one of the main components of cigarettes that can produce nicotinic interactions with antipsychotic drugs. Nicotine can also alleviate psychotic symptoms of schizophrenia. Aim: The objective for this systematic review is to examine the effects of nicotine and nicotine-based products in the treatment of schizophrenia, in comparison with placebo, no treatment or antipsychotic medication. Results: All studies comparing nicotine or other related products as the only treatment or adjunctive treatment for schizophrenia patients excluding the animal studies and case studies are reviewed. The use of traditional or known as typical antipsychotics may cause the patients to smoke frequently while patients taking atypical antipsychotics may smoke less. Patients who smoke may metabolize antipsychotics faster than non-smoking patients. There is less report related to smoking cessation among the schizophrenia patients. Conclusion: Neurobiological and psychosocial factors reinforce the high use of nicotine by patients with schizophrenia. Prior to smoking cessation implementation, it is crucial to understand on the ways and reasons for schizophrenia patients to consume nicotine for self-medicate symptoms which may lead to the development of new treatments for schizophrenia and nicotine dependence.